Sexual counseling to patients with myocardial infarction: Nurses' performance, responsibility and confidence - Tayyebeh Gazestani; Parvin Mangolian Shahrbabaki; Roghayeh Mehdipour Rabori; Mansooreh Azzizadeh Forouzi (Tehran University of Medical Sciences, 2019)
Background & Aim: One of the main concerns in patients with myocardial infarction is that there is no return to sexual activities. Sexual counseling is an interaction between patient and nurse that requires appropriate performance, responsibility, and confidence. The present study aimed to determine nurses' performance, responsibility, and confidence in sexual counseling of myocardial infarction patients. Methods & Materials: This descriptive/analytical cross-sectional study was carried out on 180 nurses from the cardiac care unit (CCU) at the hospitals located in southeastern Iran in 2018. Sampling was performed with the census method; and the data collection tool was a demographic information form and questionnaire, involving nurses' performance, responsibility, and confidence in sexual counseling of cardiac patients. Information was analyzed using SPSS software (ver.18) through descriptive and inferential statistics, including t-test, ANOVA, and Pearson correlation coefficient. The significance level was considered as 0.05.   Results: The mean of total performance scores in the nurses was 14.54 ± 4.4, indicating the average performance of nurses in the sexual counseling of myocardial infarction patients. The total mean score of responsibility was 14.32±2.7, indicating their average responsibility in sexual consultation. The total mean score of confidence was 12.86±2.35, indicating their average confidence in the sexual counseling of cardiac patients. Conclusion: The present research showed that nurses' performance and confidence were not high or acceptable in the sexual counseling of patients with a myocardial infarction, which can lead to some dangerous events such as recurrent myocardial infarction or sudden death. Thus, holding some workshops or training related to the sexual counseling of the patients can assist nurses to be better in this case.